Knowledge regarding technical aspects of non-surgical root canal treatment in Al-Madinah Al-Munawarah private dental centers - Mothanna Alrahabi; Mohmmad Sami Ahmad (Wolters Kluwer Medknow Publications, 2015)
Objective: We evaluated knowledge of technical aspects of non-surgical root canal treatment among general dentists in private dental clinics in Al-Madinah Al-Munawarah, Saudi Arabia. Materials and Methods: A questionnaire was distributed randomly to 70 general dental practitioners who were working in private dental centers. The response rate was 88.6%. Results: The results showed that only 3% of dentists were using rubber dams for isolation during endodontic treatment. The majority (59.7%) were using radiographs to determine the length. Also, 37% were using nickel-titanium (NiTi) rotary instruments to prepare the root canal. The lateral condensation technique with gutta percha points to fill the root canal was used by most respondents (77.5%). Conclusions: This study provides important data on endodontic treatment by general dental practitioners in Al-Madinah Al-Munawarah private dental centers. It shows a general lack of knowledge regarding the importance of using rubber dams as well as the new endodontic materials and methods. Continuing education programs to update their knowledge in the field of endodontics are essential.